The Euro Zone Eastern Enlargement: Challanges to Current Members and the ECB - Mihai Sebea (Romanian Journal of European Affairs)
The eastward enlargement of the euro area entails significant implications both for acceding countries and for the current euro area member States or for the European Central Bank. The present analysis intends to assess the challenges up against the latter. The issue is analyzed from two points of view: firstly, relating to the risks caused by the group’s drawing away from the status of optimum currency area, complemented by increasing development disputes and the difficulty of implementing a unique currency policy, and secondly – the issue of the voting mechanism within the ECB. When analyzing those two issues, we can easily notice that the difficulties for ECB and even for the actual euro zone member will increase. Since the extended euro zone will draw away from the status of optimum currency area, the costs of the monetary unification will increase for the new group as a whole (not only for the new members). Moreover, for the new euro zone, which is becoming more divergent, it will be very hard to find suitable monetary policy instruments for all. With reference to the second subject, the ECB will implement a new voting mechanism, but this will not solve the problem of having large economies with weak representation, and small economies that have strong representation in the Governing Council.